Methodological contributions of Social Neuroscience for the study of multimodality in translation - Chica Núñez, Antonio Javier (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2019)
This study analyses the interplay of various communication modes that enables emotions to be transmitted efficiently from source (ST) to target text (TT) in audio description (AD) as a multimodal text. It draws on existing experimental designs, including neutral or emotional conditions based on the congruency of stimuli from various modes (images, dialogue semantic content or prosody in a film, together with the semantic content of AD). This article reviews the methodological contribution that Social Neuroscience could make to the study of multimodal translation. To this end, some neurobiological models and studies are quoted regarding multimodal emotional information processing (Brück, Kreifelts, & Wildgruber, 2011), the impact of multimodal emotional processing on subjects’ empathy (Regenbogen et al., 2012) and the dynamics of neural networks involved in human empathy and communication through the presentation of multimodal stimuli (Regenbogen, Habel, & Kellerman, 2013). Finally, an experimental design that focuses on the transfer of feelings and emotions in film AD, which would be suitable for a potential pilot study, is presented.